(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Itch and disruption of the skin’s natural barrier function are major contributors to issues in children with atopic dermatitis, including those that impact their ability to sleep, which in turn affects their ability to function or impacts their caregivers’ ability to function. We sought to determine how often these issues occurred in a week, how severe they were, and what factors were associated with itch and sleep issues in a pediatric population. Methods We conducted a cross-sectional study of children <17 years of age with confirmed atopic dermatitis. We utilized a seven-question tool to determine how often the symptoms occurred in a week and how severe they were. We also utilized a tool to determine how often the itch occurred, how severe it was (0 to 10 scale), how often the sleep issues occurred, and a pediatric sleep tool to determine how severe the sleep issues were (clinically significant sleep issues were defined as a score of 41 or higher). We also determined domain-weighted mean scores (0 to 3 scale) for frequency data. We utilized chi-square, one-way ANOVA for comparison, Spearman’s rho for correlation, and binary logistic regression to determine predictors of daily itch and clinically significant sleep issues. Results We identified that 55% of our population reported clinically significant sleep issues, 35% reported daily itch, and that itch was present 4 out of 7 nights per week, with a severity of 6 out of 10. We also identified that clinically significant sleep issues were associated with daily itch (p < 0.001), age (p < 0.001), and severity of itch (p < 0.001), as well as a negative correlation with domain-weighted mean scores for frequency Parental sleep was more disturbed, from 1.2 to 7.8 (p < 0.001). Sleep sub-scores worsened, from 0.5 to 3.7 (p < 0.001). Symptom burden was greatest for dry/rough skin, then for itching, then for cracking, and least for weeping/oozing, then for bleeding. It was associated with 49.2% daily for dry/rough, 28.2% daily for itching, 23.7% daily for cracking, 5.9% daily for weeping/oozing, and 4.8% daily for bleeding. It was associated with an average of 15.44. Conclusion Itching and skin barrier issues were the most common each week and were strongly associated with sleep problems in a dose-dependent manner. Increasing duration of disease and barrier symptom burden were related to daily itch and clinically significant sleep problems. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S325-S335